The Effectiveness of Problem Based Learning in Terms of Creativity and Learning Outcomes - Rohmah Nila Farida; Dwi Priyo Utomo; Zukhrufurrohmah Zukhrufurrohmah (MEJ (Mathematics Education Journal), 2020)
This study aims to describe the effectiveness of Problem Based Learning in terms of student creativity and student learning outcomes. This research is located at Prigen Prosperous Middle School in the even / odd semester of the 2019/2020 school year. This type of research uses the type of descriptive research with descriptive qualitative research methods with research subjects VII grade students of Prosperous Prosperous Middle School. The steps in this research are determining the problem, conducting a literature study, determining the location, determining the method, data collection, and data analysis. In this study, the average percentage of the learning achievement in the preliminary activities was 92.21%, the core activities were 96.41% and the closing activities were 81.47% so that overall the learning implementation was categorized as very good. The average percentage of students' creativity is 82.0% with a very good category. The average percentage of student learning outcomes students 81.81% with a very good category. Based on the description, Problem Based Learning is effective in terms of students' creativity and learning outcomes.